Alpha-actinin isoform and skeletal muscle activity - Yuji Ogura; Ryo Kakigi; Hisashi Naito (Journal of Physical Fitness and Sports Medicine, 2013)
Alpha (α)-actinin is an actin-binding protein in mammalian cells. In skeletal muscles, α-actinin is located in the Z-line of sarcomeres, where it creates actin-actin crosslinks. We have recently reported that α-actinin adaptation occurs at the isoform level in rat skeletal muscle under different physiological conditions in an isoform-specific manner. Based on those results, this review briefly summarized the effects of changes in muscle activity on α-actinin expression.